Analisis perbandingan kinerja keuangan berdasarkan psak 23 dan psak 72 mengenai pendapatan pada perusahaan manufaktur - Siwi, Trianggunani Purnaning; Kartika, Andi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research was conducted to analyze the comparison of financial performance based on PSAK 23 and 72 regarding earnings in manufacturing companies. This research was conducted in the manufacturing sector because it is considered as one of the sectors that have an impact on the issuance of PSAK 72 and replaces the rules of PSAK 23 which were previously used by this sector. This research is a comparative study using quantitative descriptive analysis techniques and sample collection techniques by collecting secondary data on pharmaceutical subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) with certain criteria through the financial statements of each company using the SPSS version 26 program. The population used in this study is the pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2020. The results of this study show that only in the price accounting ratio there is a significant difference when implementing PSAK 72. With the new rules regarding PSAK 72, can make financial statements with real / real income, due to income that has not been completed with transactions, so it cannot be recognized as income. Therefore, the value of revenue in 2020 for each company will be smaller than the value of revenue when it was still applying PSAK 23.